Educação das relações étnico-raciais: processos educativos decorrentes do brincar na educação infantil - Oliveira, Alessandra Guerra da Silva (2015)
This research seeks to understand the educational processes arising from the social practice on playing on a guided intervention and for the Education of Racial-Ethnic Relations in a kindergarten classroom, in compliance with the Law 10639/03 establishing the mandatory theme regarding the African and Afro-Brazilian history and Culture in basic education and the fight against racism and discrimination. The study was developed with children aged 2-3 years in a public municipal school in São Carlos / SP. This is a qualitative research developed based on the assumptions of phenomenology, thus seeking to understand the phenomenon from the social practice of playing. As an instrument to record the data we used the field diaries, we also used a log (register) book to keep a constant dialogue with the parents and children s research collaborators responsible. From the observations systematically recorded by the researcher in the field diaries, it was possible to form three categories of analysis: A) Playing and knowing the history and culture of the afro-Brazilian and African; B) Playing and building positive ethnic-racial identity; C) Playing, talking and learning. This allowed the completion of the results construction. From these considerations we present the understanding that the Education regarding Racial-Ethnic Relations yet come to making effective in early childhood education schools and, through the intervention and experiences with african-Brazilian and African history and culture was increased interaction and dialogue between all the participants, children showed a significant increase in self-esteem in addition to having been an appreciation of ethnic and racial identity; all that was experienced in the intervention was reproduced by children in other practices and moments.